Analisis Pengawasan Oleh Kantor Otoritas Bandar Udara Wilayah V Makassar Terhadap Delay Management Maskapai Garuda Indonesia Di Bandar Udara Internasional Sultan Hasanuddin Makassar - Ingrit Nisriani Lisa Mengkanna; Teguh Ariebowo (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The airport authority is surveillance, the surveillance process is three (3) kinds of observation, inspection and monitoring and subject of control in the air transport area, one of which is delayed management. Management control control is regulated by 2015 minister number 89 on handling flight delays, surveillance activities carried out by air freight inspectors. The aim of the study is how the management delay and treatment will be conducted by the v makassar regional airport authority office. The study uses qualitative research methods by using primary and secondary data. Data collection techniques of observation, interview and documentation. Time and place on this study began on October 01, 2022 and April 20, 2023, it was carried out at the v makassar regional airport authority office. The data analysis techniques used are data collecting, data reduction, data presentation, deduction. The validity test of data on this study employed the method of technical triangulation and data source triangulation.The study shows that the management control activities of the airport authorities on delayed management by the air freight section of the air freight inspector, the monitoring is done on a schedule or monthly basis for all airlines operating. The study also found obstacles to the delay of compensating passengers and delay of data information delay to the air transit inspector. Handling of delay management will be reported to the central directorate through several processes and will be followed through with the 27year 2021 ministry regulation, on the monitoring and enforcement of administrative sanctions against infractions.